Mineralização da matéria orgânica de lodo aplicado no solo e produtividade do capim-tifton 85 - Diogo André Pinheiro da Silva (2017)
The objective of this work was to evaluate and quantify the organic matter mineralization of organic waste from septic tank (LTS), anaerobic digester (LDA), UASB reactor (LRU) and material withdrawn at different depths in the residue layer (SAC-EV), in addition to the productivity of Tifton 85 grass, in a Red Yellow Argisol fertilized with these organic materials, with the application rate equivalent to 300 kg ha-1 year -1 of nitrogen (NT) in the University Federal of Minas Gerais (UFMG), and in climatic conditions controlled by the respirometric method, at the Laboratory of Physical and Chemical of the Department of Sanitary and Environmental Engineering (DESA), at the equivalent doses of 300 kg ha-1 year - 1 of NT and 600 kg ha-1 year -1 of NT. The different types of residues were collected at the Sewage Treatment Plant of Ribeirão Arrudas (ETE - Arrudas) and at the Center for Research and Training in Sanitation (CePTS - UFMG / COPASA). Among the ways of obtaining the value of the fraction of mineralization (FM), using the adjusted equations of the kinetic decay model of two phases, was the one that generated results that are more reliable. Thus, the FM values of the organic material, considering the mineralized organic carbon values (COTmin), estimated at 215 days of degradation under field conditions, were 93 to 100% in the LSACEVs, 97% in the LRU and LTS and 69% in LDA; when COfo, was considered 96 to 100% in LSAC-EVs, 99% in LRU and LTS and 83% in LDA. When considering organic nitrogen (NO) as a reference, FM values ranged from 92 to 100% in the LSAC-EV, LDA and LTS and 87% in the LRU. The values of FM quantified in the respirometry test for the dose of application of the organic residues equivalent to 300 kg ha-1 year -1 of NT, were 50 to 79% in the LSAC-EVs and 53; 88 and 90% respectively in the LRU, LTS and LDA. In relation to the dose of 600 kg ha-1 year -1 of NT, the FM values were 26 to 79% in the LSAC-EVs and close to 100% in the other residues. In field conditions, the FM values were higher than observed under the conditions controlled, in the laboratory. The incorporation of the residues in the soil contributed to the increase of up to 15, 8 times in the yield of Tifton 85 grass, in relation to the control (without fertilization). Based on the results obtained for the mineralization fractions and in the operational history of the LSAC-EV, concluded that the time of the septic tank sludge in the SAC-EVs should be greater than 1 year and may extend for longer, taking since in this period the material reaches greater stabilization and still maintains its value as an agricultural fertilizer.